X-ray diffraction and biocompatibility of glass ionomer cement reinforced by different ratios of synthetic hydroxyapatite - Mohammed R Al.Jabouri; Zainab Zabar Abdul-Ameer (College of Dentistry/ University of Baghdad, 2014)
Background: This study was done to assist X-ray diffraction and biocompatability of glass ionomer cement reinforced by different ratios of Hydroxyapatite. Materials and Methods: The powder of glass ionomer cement reinforced by different ratios of Hydroxyapatite were used to get X-ray diffraction pattern by X-ray diffraction machine, While for biocompatibility test, A polyethylene tubes containing glass ionomer cement reinforced by different ratios of Hydroxyapatite were implanted on the dorsal submucosal site of Rabbit's tissues and histological slide were prepared for histopathological study. Results: X-ray diffraction test showed that all elements of glass ionomer cement reinforced by different ratios of Hydroxyapatite were react with each other and all the final products none crystalline in nature with small amount of Hydroxyapatite present unreacted may be act as cores for final reacted elements. The histological test showed mild irritation to Rabbit's tissues by glass ionomer cement reinforced by different ratios of Hydroxyapatite, this irritation subsided with time. Conclusions: there is chemical reaction of all elements of glass ionomer cement reinforced by different ratios of Hydroxyapatite and new final products were results .Also glass ionomer cements reinforced by different ratios of Hydroxyapatite were biocompatible with Rabbits tissues.